Determination of Antioxidant Activity of Total Flavonoids from Tussilago farfara by Flow Injection Chemiluminescence - Liu1, Caihong; Qin2, Kun; Qi1, Yongxiu; Li1, Ke; Li1, Yuqin; Jia1, Baoxiu (Asian Journal of Chemistry, 2013)
The antioxidant activity of total flavonoids from Tussilago farfara in vitro was determinated by flow injection analysis chemiluminescence. The determination was based on the inhibition effect of their natural antioxidants on the free radical-induced luminol chemiluminescence. Ascorbic acid was used as antioxidant standard. At the optimum operational conditions, the antioxidant activity was measured by plotting the inhibition percentage versus the content of samples to calculate the IC50. The results revealed that the flavonoids from Tussilago farfara showed stronger free radical scavenging activity on superoxide (O2–•) than ascorbic acid. It is suggested that Tussilago farfara is a good natural antioxidant and has the potential to be used in the manufacturing of foods and medicines.